ANALYSIS STUDY OF COASTAL RECLAMATION IMPACT TO THE NATIONAL RESILIENCE (A LITERARY, PHILOSOPHICAL, JURIDICAL AND SOCIOLOGICAL APPROACH) - Dewi Yustiana; Mohammad Fadli; Adi Kusumaningrum; Solimun Solimun (Indonesian Naval Technology College STTAL, 2021)
Coastal reclamation is an effort to establish a new land area in the coastal area. The main objective of reclamation is to turn the untapped coastal area into a new area that is better for various people's lives, such as residential, industrial, airport, waste and environmental management areas, tourist areas, and other strategic purposes. Reclamation is carried out to increase the benefits of land resources from a socio-cultural, economic, and environmental point of view by utilizing the land to become more useful. Several cases of coastal reclamation, such as the reclamation of the north coast of Jakarta, the coast of Makassar, and Benoa Bali, have raised pros and cons and have had a significant impact on the lives of local communities, especially on environmental, economic, and socio-cultural aspects. This is very influential on the condition of the National Resilience of the Indonesian nation, especially the area. This research aims to conduct a comprehensive study of the impact of coastal reclamation on National Resilience. Activities start from a comprehensive understanding of the system that occurs through a critical review of previous research. As for based on preliminary observations and critical studies of previous research, which is followed by the preparation of significant factors from the environmental, economic, and socio-cultural aspects. Each aspect is analyzed its role in the National Resilience system as a result of Reclamation. In the final section, an analysis of physiological, juridical, and sociological approaches is carried out to strengthen the research results. Keywords: Analysis Study, Coastal Reclamation, National Resilience